Pablo Bertinat, Eduardo D’Elia, Roberto Ochandio, Maristella Svampa, Enrique Viale y Observatorio Petrolero Sur (2014). 20 mitos y realidades del fracking - Martínez, Andrea (Revista Economía, 2019)
Reseña de "20 mitos y realidades del fracking"